Currency competition in the Eurozone: An answer to the crisis - Krzysztof Spirzewski (e-Finanse: Financial Internet Quarterly, 2016)
The common currency was created as a result of theoretical considerations regarding the functioning of optimum currency areas. This theory refers to a number of benefits as well as costs. It imposes a number of requirements that are necessary for the newly created structure to be considered optimum. The economies of Eurozone countries did not meet these requirements. In consequence, the present functioning of the Eurozone encounters many disturbances - the strong differentiation of the balance of payments is a signifi cant example. The reforms initiated in the European Union and undertaken in response to the financial crisis encompassed the Eurozone countries, yet they only concern financial policy. The adopted strategy of action arouses questions as to its effectiveness. The aim of this article is to present one of the reasons for the Eurozone crisis and a proposal for changing the monetary policy, in particular the exchange rate. In view of this objective, the main hypothesis reads as follows: one of the methods of counteracting the crisis is to introduce currency competition within the Eurozone.
Keywords: E02; E52; G01; 330; European Union; Currency Competition; Financial Crisis